Wildtype peers rescue social play and 50-kHz ultrasonic vocalization deficits in juvenile female Cacna1c heterozygous rats - Bogdan, Rebecca; Kayumova, Rukhshona; Schwarting, Rainer K. W.; Wöhr, Markus; Kisko, Theresa M. (Frontiers in Behavioral Neuroscience, 2023)
Healthy brain development depends on early social practices and experiences. The risk gene CACNA1C is implicated in numerous neuropsychiatric disorders, in which key characteristics include deficits in social functioning and communication. Recently, we reported sex-dependent impairments in social behavior and ultrasonic vocalizations (USV) in juvenile heterozygous Cacna1c+/-(HET) rats. Specifically, HET females displayed increases in rough-and-tumble play that eliminated the typically observed sex difference between male and female rats. Interestingly, female wild-type Cacna1c+/+ (WT) pairs also showed a similar increase in social play when housed with HET females, suggesting their behavior may be influenced by HET cage mates. This indicates that the genetic makeup of the social environment related to Cacna1c can influence social play, yet systematic studies are lacking. Cacna1c 2 Consequently, in the present study, we housed juvenile females in MIXED-or SAME-genotype cages and tested them in a social play paradigm with a same-and opposite-genotype partner. The results show that the early social environment and the genotype of the play partner influence social play and 50-kHz USV emission. Experience with a WT play partner appears necessary for HET females to show comparable levels of play and 50-kHz USV emission. Same-genotype HET pairs played less and emitted fewer 50-kHz USV than same-genotype WT or opposite-genotype pairs; however, we found that the decrease in social play and 50-kHz USV in HET pairs can be rescued by playing with a WT partner. The effect was particularly prominent when the first play partner was WT, as we found it increased play and 50-kHz USV emission in all subsequent interactions with ensuing partners. These findings suggest that the genetic makeup related to the social environment and/or social peers influences social play in Cacna1c haploinsufficient rats. Specifically, our results show that WT peers can rescue behavior and communication alterations in Cacna1c female rats. Our findings have important implications because they show that the genetic makeup of the social environment can divulge phenotypic changes in genetic rat models of neuropsychiatric disorders.